Long-term and short-term outcomes of robot- versus video-assisted anatomic lung resection in lung cancer: a systematic review and meta-analysis. (23rd December 2020) - Wu, Han; Jin, Runsen; Yang, Su; Park, Bernard J; Li, Hecheng
Abstract: : OBJECTIVES: Minimally invasive thoracic surgery has evolved with the introduction of robotic platforms. This study aimed to compare the long-term and short-term outcomes of the robot-assisted thoracic surgery (RATS) and video-assisted thoracic surgery (VATS) for anatomic lung resection. METHODS: We searched published studies that investigated RATS and VATS in anatomic lung resection. Long-term outcomes (disease-free survival and overall survival) and short-term outcomes (30-day mortality, postoperative complications, conversion rate to open surgery and lymph node upstaging) were extracted. The features were compared and tested as hazard ratios (HRs) and odds ratios (ORs) at a 95% confidence interval (CI). RESULTS: Twenty-five studies with 50 404 patients (7135 for RATS and 43 269 for VATS) were included. The RATS group had a longer disease-free survival than the VATS group (HR: 0.76; 95% CI: 0.59–0.97; P = 0.03), and the overall survival showed a similar trend but was not statistically significant (HR: 0.77; 95% CI: 0.57–1.05; P = 0.10). The RATS group showed a significantly lower 30-day mortality (OR: 0.55; 95% CI: 0.38–0.81; P = 0.002). No significant difference was found in postoperative complications (OR: 1.01; 95% CI: 0.87–1.16; P = 0.94), the conversion rate to open surgery (OR: 0.92; 95% CI: 0.56–1.52; P = 0.75) and lymph node upstaging (OR: 0.89; 95% CI: 0.52–1.54; P = 0.68). CONCLUSIONS: RATS has comparable short-term outcomes and potential long-term survival benefits for anatomic lung resection compared with VATS.